2015
DOI: 10.1080/00268976.2015.1086834
|View full text |Cite
|
Sign up to set email alerts
|

Bucky-corn: van der Waals composite of carbon nanotube coated by fullerenes

Abstract: Can C60 layer cover a surface of single-wall carbon nanotube (SWCNT) forming an exohedral pure-carbon hybrid with only VdW interactions? The paper addresses this question and demonstrates that the fullerene shell layer in such a bucky-corn structure can be stable.Theoretical study of structure, stability and electronic properties of the following bucky-corn hybrids is reported: C 60 and C 70 molecules on an individual SWCNT, C 60 dimers on an individual SWCNT as well C 60 molecules on SWNT bundles. The geometr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…In addition, CNTs-networks decorated by nanometric C 60 crystals are expected to be useful for templating the nano-morphology of the active layer in bulk-heterojunction organic photovoltaics (OPV) [9] devices: the nano-crystals may serve as nucleation sites for the fullerenes (or fullerene derivatives) and prevent their coarsening into micron-sized crystallites thus retarding the degradation of the active layer in bulk-heterojunction polymer-fullerene devices, while the CNT may serve as nucleation sites for the conjugated polymers [10] . In spite of theoretical predictions [11,12] , experimental realization of exohedral non-covalent hybridization of pristine, unmodified C 60 fullerenes and CNTs was not reported yet. In our perspective, the relatively strong inter-fullerene and inter-tube interactions [13] that drive the system toward phase separation and the formation of fullerene crystals and CNTs bundles are the main obstacle toward controlled assembly of non-covalent hybrids of pristine CNTs and C 60 fullerenes.…”
mentioning
confidence: 96%
“…In addition, CNTs-networks decorated by nanometric C 60 crystals are expected to be useful for templating the nano-morphology of the active layer in bulk-heterojunction organic photovoltaics (OPV) [9] devices: the nano-crystals may serve as nucleation sites for the fullerenes (or fullerene derivatives) and prevent their coarsening into micron-sized crystallites thus retarding the degradation of the active layer in bulk-heterojunction polymer-fullerene devices, while the CNT may serve as nucleation sites for the conjugated polymers [10] . In spite of theoretical predictions [11,12] , experimental realization of exohedral non-covalent hybridization of pristine, unmodified C 60 fullerenes and CNTs was not reported yet. In our perspective, the relatively strong inter-fullerene and inter-tube interactions [13] that drive the system toward phase separation and the formation of fullerene crystals and CNTs bundles are the main obstacle toward controlled assembly of non-covalent hybrids of pristine CNTs and C 60 fullerenes.…”
mentioning
confidence: 96%
“…It was confirmed that physical mixing of C 60 with CNTs slightly influenced the properties of CNTs compared to covalent hybrid structure. In fact, in the mixture, C 60 molecules were attached to the CNTs surface by van der Waals forces 38,39 .…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the fact that they reproduced SWCNTs installed in a polymer lattice considering the interphase too, they did not supplant a SWCNT and its encompassing polymer with a comparable fibre. A few scientists built their displaying systems in light of the basic mechanics approach [65,68,71,74,77] initially created by Li and Chou [63]. The FEM displayed beforehand by Li and Chou was altered by To [71], with the impact of Poisson's proportion incorporated into deciding the Young's and shear moduli of SWCNTs.…”
Section: Resultsmentioning
confidence: 99%
“…Tserpes and Papanikos [74] used a similar reproduction approach of Li and Chou [63] by utilizing a 3-D pillar component worked in the ANSYS business FEM bundle. Kalamkarov et al [65] likewise utilized the demonstrating method of Li and Chou in the numerical piece of their examination to anticipate the Young's modulus of single-walled, twofold walled and multiwalled CNTs (MWCNTs) by utilizing the ANSYS bundle. Besides, they built up a scientific strategy in light of the asymptotic homogenization, on the system of a tube-shaped shell and contrasted the outcomes acquired, and those found by a limited component investigation.…”
Section: Resultsmentioning
confidence: 99%